Determination of Au and Ag from iron ores combining FA and ICP/AES methods - Dragan Tošković; Miloš Rajković (Zaštita Materijala)
In this paper, the combination of FA (Flame Analysis of Noble Metals - Cupellation) and ICP/AES (Atomic Emission Spectrometry with Induction Coupled Plasma) methods for determination of Au and Ag in geological samples of iron ore-magnetite was presented. Au and Ag were concentrated with Pb from PbO after desulphurisation and melting process (Pb2+→Pb). Regulus (Pb with noble metals) is then cupellated. The resulting bead-pril after cupellation was dissolved in HNO3 and then in HCl (imperial water: 2HNO3 and 6HCl). After the preparation of standard solutions and a blank test, the ICP/AES recording is performed. The obtained results were compared with those obtained by the classical method of cupellation. The advantages of ICP/AES are excellent detection limits and linear dynamic range as well as a stable and repeating signal which is particularly important for samples of iron tested due to the low content of noble metals.